Opportunities of implementing the genomic selection in small populations - the Croatian case - Špehar, Marija (Array, 2019)
The implementation of genomic selection (GS) together with the changes caused by globalization and trade liberalization of breeding material often raise the question of sustainability of breeding programs in small cattle populations/countries. The objective of this study was to describe the steps in the implementation of GS in small populations of Croatian Simmental (SIM) and Holstein (HOL) breeds; to show the results of its implementation; and to present the perspectives of GS for these populations. In order to improve the selection of SIM bulls, Croatia joined the German-Austrian genomic evaluation system in July 2013. The main goal of the GS in HOL population was selection of bull’s dams at a young age which started in 2016 through the inclusion in German HOL genomic evaluation system. In total, 268 SIM and 96 HOL calves were selected, genotyped, and genomically tested until the end of 2017. The criterion for the entry of SIM bulls in the artificial insemination (AI) centres is the total merit index over 130 and candidates should not be carriers of specific monogenic defects or be recessive for them. Based on these criteria, seven young bulls were selected as for AI. The criteria for the selection of HOL females are the total merit index of 150, without monogenic defects and so far none of them reached these standards. The future perspective for HOL breed is international IgHol project for small HOL populations representing the possibility for cost-efficient solutions of GS. The implementation of GS brought opportunity to Croatian breeders to use semen of bulls from the national breeding program. Genomics for females becomes an attractive option to capitalise the benefits of using this technology.